Implementasi Kurikulum Merdeka Belajar dalam Kegiatan Proses Belajar Mengajar SMP Tahun Ajaran 2023/2024 - Barthon Wenda; Andinus Yanengga; Amos Rombe; Marlince Anggelina Siep; Christine M Rumpaisum; Elen Kogoya (PT PUSTAKA CENDEKIA GROUP, 2024)
This curriculum is one of the learning programs to improve the quality of learning that has been inaugurated by the Minister of Education and Culture which has been established in the world of education. The purpose of this study is (1) to explain the conditions of students if the independent curriculum is implemented in each school (2) To find out whether the principal and teachers are ready to implement the independent curriculum in schools or not (3) To find out the factors that become obstacles. in the implementation of this independent curriculum. This study uses a descriptive qualitative approach by taking objects from three schools, namely Ibele State Middle School, Wamena 4 State Middle School, and Isakusa State Middle School. Data collection techniques are carried out through observation, interviews and documentation. The respondents in this study were the principals. The results of the study showed that the new independent curriculum was implemented this year (2024), odd semester in class VII. Where the readiness of the teachers is ready and some are not ready because there are some teachers who did not attend the training. So that the principal for the next few months held a socialization about the independent curriculum to teachers who did not attend the training, even from SMP Negeri 4 Wamena the principal provided Kombel (Learning Community). Likewise in the teaching and learning process that has been known about the condition of students where in their own personalities some do not know how to read and write, so the efforts made by the teacher are to separate students who are still lacking in reading and writing, to be guided and trained and taught how to read and write while the problem is the infrastructure, and one of them is electricity that has not entered the SMP Negeri Ibele area, so from several things this is the obstacle.